Development of a Holistic Nursing Model Based on Transcultural Nursing to Improve the Quality of Life of Patients with Type-2 Diabetes Mellitus - Suniyadewi, Ni Wayan; Arief, Yuni Sufyanti; Kurniawati, Ninuk Dian; Rismayanti, I Dewa Ayu; Trisnadewi, Ni Wayan; Iswatun, Iswatun (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2024)
Background: The management of type 2 diabetes mellitus (T2DM) primarily emphasizes physical care, yet the quality of life (QoL) remains suboptimal. The management of diabetes often neglects psychological, socio-cultural, and spiritual aspects, which are essential components of transcultural nursing. Developing a holistic nursing model rooted in transcultural nursing, which has never been broadly investigated, is imperative to enhance QoL in individuals with T2DM.Purpose: This study aimed to develop a nursing model based on transcultural nursing to enhance the QoL of individuals with T2DM.Methods: This study employed a quantitative research design with a cross-sectional approach. A sample of 145 individuals with T2DM was recruited using a simple random sampling technique. A self-developed questionnaire was used, incorporating factors from Dossey’s holistic nursing model, Leininger’s transcultural nursing model, and a QoL questionnaire. Inferential statistics using smart PLS-structural equation modeling (SEM) were employed for data analysis.Results: The findings revealed that the holistic nursing model based on transcultural nursing in individuals with T2DM was influenced directly by respondent characteristics (t=3.313, p=0.001), religious and life philosophy (t=2.836, p=0.005), social and kinship (t=2.579, p=0.010), cultural and lifestyle (t=2.833, p=0.005), biological (t=2.718, p=0.007), and psychological (t=2.497, p=0.013) factors. However, the technological factor was not significantly (t=0.802, p=0.423) associated with the model. The holistic nursing model based on transcultural nursing had a direct influence on the quality of life (t=9.124 and p=0.000).Conclusion: The holistic nursing model based on transcultural nursing encompasses six variables: respondent characteristics, religious and life philosophy, social and kinship, cultural and lifestyle, and biological and psychological factors. The model can serve as a guideline for managing type 2 DM patients to enhance the QoL.